Fluorine resin-coated steel plate
Patent Information
- Application Number
- JP2024231367
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-07-28
AI Technical Summary
【0015】 本発明によれば加工性や耐候性等の他の物性を良好に維持しつつ、経時加工性に優れた塗装鋼板を提供できる。
Smart Images

Figure 2025036664000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated steel sheet having excellent aging formability. [Background technology]
[0002] Hot-dip Al-Zn plated steel sheet (hereinafter sometimes referred to as "55% Al-Zn plated steel sheet"), which has a standard composition in which the plating layer contains approximately 55 mass% Al, approximately 1.6 mass% silicon, and the remainder is zinc, has shown excellent corrosion resistance and, therefore, demand for it has been increasing in recent years, mainly in the field of building materials. Furthermore, fluororesin-coated steel sheets, which are made by coating 55% Al-Zn-plated steel sheets with a fluororesin coating, are used as wall materials for houses and stores as metal siding, combining complex patterns shaped with interlocking shapes to imitate stone or wood using an embossing roll, due to the excellent workability and weather resistance of fluororesin.
[0003] As a fluororesin-coated steel sheet, for example, Patent Document 1 discloses a coated metal sheet in which a topcoat layer containing a specific vinylidene fluoride resin is formed on the uppermost surface of a metal sheet having a chemical conversion treatment layer on the surface and a primer layer on the top of the chemical conversion treatment layer. For example, as described in Patent Document 1, vinylidene fluoride resin is a thermoplastic resin, and by suppressing crystallization by rapid cooling after baking and making it amorphous, it is possible to exhibit excellent processability.
[0004] Furthermore, for example, Patent Documents 2 to 4 disclose techniques for improving scratch and wear resistance while maintaining excellent processability by using glass flakes, ceramic fibers, silicon carbide powder, acrylic polymer beads, tetrafluoroethylene resin powder, etc. as materials constituting the topcoat layer.
[0005] However, although such fluororesin-coated steel sheets have a certain degree of effect in improving workability and weather resistance as described above, there is a problem in that the fluororesin crystallizes over time, causing a deterioration in workability (problem of workability over time).
[0006] Therefore, various techniques have been investigated to solve the problem of the aging processability of fluororesin-coated steel sheets. For example, Patent Document 5 discloses a technique in which fine fluororesin particles of 5 μm or less are used as a material for forming the topcoat layer to promote compatibility with acrylic resin and suppress crystallization of the fluororesin. However, although the technology of Patent Document 5 can improve processability to a certain extent, crystallization cannot be sufficiently suppressed in the fluororesin topcoat layer after about three months, and cracks occur in the topcoat layer at the severely processed portions during embossing roll processing in siding molding. Therefore, there is still a need to develop a technology that can improve processability over time. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 1853338 [Patent Document 2] JP 2001-137775 A [Patent Document 3] Publication No. 2003-71980 [Patent Document 4] Japanese Patent Application Publication No. 9-221621 [Patent Document 5] Japanese Patent Application Publication No. 6-262139 Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above circumstances, an object of the present invention is to provide a coated steel sheet that has excellent aged workability while maintaining other physical properties such as workability and weather resistance at a good level. [Means for solving the problem]
[0009] The inventors conducted research to solve the above-mentioned problems regarding fluororesin-coated steel sheets in which a chemical conversion coating and a primer layer, as well as a topcoat layer containing a fluororesin, are formed on a hot-dip Al-Zn-plated steel sheet. As a result, they found that by specifying the mass ratio of the polyvinylidene fluoride resin constituting the topcoat layer within a specific range and by containing an inorganic filler that is effective as a crack propagation inhibitor and an organic aggregate that is effective as a stress relaxation agent in the topcoat layer, it is possible to suppress crack propagation in the topcoat layer and ensure flexibility, regardless of whether the fluororesin crystallizes, and therefore it is possible to achieve excellent aging workability while maintaining other physical properties such as workability and weather resistance at a good level.
[0010] The present invention has been made based on the above findings, and the gist of the present invention is as follows. 1. A coated steel sheet having a chemical conversion coating, a primer layer and a topcoat layer formed on a hot-dip Al-Zn-plated steel sheet, The top coat layer includes a resin component containing a polyvinylidene fluoride resin and an acrylic resin, the polyvinylidene fluoride resin being present in an amount of 50 to 80% by mass; A color pigment; 0.1 to 20 mass% of an inorganic filler having an average particle size of 1 to 30 μm and an aspect ratio of 5 or more; Average grain size is 1 to 35 μm and micro Vickers hardness is 50 HV 0.05 0.1 to 15 mass% of organic aggregate, A fluororesin-coated steel sheet comprising:
[0011] 2. The fluororesin-coated steel sheet according to item 1 above, wherein the total content of the inorganic filler and the organic aggregate in the top coat layer is 0.2 to 35 mass %.
[0012] 3. The fluororesin-coated steel sheet according to 1 or 2, characterized in that the coating layer of the hot-dip Al-Zn-coated steel sheet contains 20-95 mass% Al, 1-3 mass% Si, and 5 mass% or less of optional added components, with the remainder being Zn and unavoidable impurities.
[0013] 4. The fluororesin-coated steel sheet according to 3 above, characterized in that the plating layer contains 50-60 mass% Al, 1-3 mass% Si, and 5 mass% or less of optional added components, with the remainder being Zn and unavoidable impurities.
[0014] 5. The plating layer has a dendritic phase and an interdendritic phase, and the Vickers hardness of the dendritic phase is 10 to 110 HV. 0.1 5. The fluororesin-coated steel sheet according to the above item 3 or 4, Effect of the Invention
[0015] According to the present invention, it is possible to provide a coated steel sheet which is excellent in workability over time while maintaining other physical properties such as workability and weather resistance at a good level. [Brief description of the drawings]
[0016] [Figure 1] 1 is a cross-sectional view that illustrates a cross section of one embodiment of a fluororesin-coated steel sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the fluororesin-coated steel sheet of the present invention will be described with reference to the drawings as necessary. Note that each component shown in the drawings is shown diagrammatically for the convenience of explanation, and some parts may differ from the actual dimensions and shapes.
[0018] The fluororesin-coated steel sheet of the present invention (hereinafter sometimes referred to as "the coated steel sheet of the present invention") is a coated steel sheet having a chemical conversion treatment layer 20, a primer layer 30 and a top coat layer 40 formed on a hot-dip Al-Zn-plated steel sheet 10, as shown in Figure 1. The top coat layer 40 includes a resin component 41 containing polyvinylidene fluoride resin and acrylic resin, and the mass ratio of the polyvinylidene fluoride resin is 50 to 80%; A color pigment (not shown); 0.1 to 20 mass % of inorganic filler 42 having an average particle size of 1 to 30 μm and an aspect ratio of 5 or more; Average grain size is 1 to 35 μm and micro Vickers hardness is 50 HV 0.05 The organic aggregate 43 is 0.1 to 15 mass%. The present invention is characterized by comprising:
[0019] The topcoat layer contains inorganic filler 42 having an average particle size of 1 to 30 μm and an aspect ratio of 5 or more, so that the inorganic filler 42 can act as a crack propagation inhibitor. 0.05 By including the organic aggregate 43 described below, the organic aggregate 43 can act as a stress relaxant. This can suppress the propagation of cracks that occur from the surface layer side of the top coat 40 when the coated steel sheet is bent, and can also distribute the tensile stress applied to the top coat layer 40 to suppress the occurrence of cracks, resulting in the fluororesin coated steel sheet of the present invention being able to achieve excellent aging resistance. Incidentally, by containing a certain amount of polyvinylidene fluoride resin in the topcoat layer 40 (50 to 80% by mass in the base resin), it is possible to maintain good processability, weather resistance, and the like.
[0020] Hereinafter, each member constituting the fluororesin-coated steel sheet of the present invention will be described. As described above, the fluororesin-coated steel sheet of the present invention has a chemical conversion layer 20, a primer layer 30 and a top coat layer 40 formed on a hot-dip Al-Zn-plated steel sheet 10, and has a chemical conversion layer 20, a primer layer 30 and a top coat layer 40 formed on the hot-dip Al-Zn-plated steel sheet 10.
[0021] (Hot-dip Al-Zn coated steel sheet) The fluororesin-coated steel sheet of the present invention uses a hot-dip Al-Zn-plated steel sheet as the steel sheet, which can ensure high corrosion resistance. Here, the type of the hot-dip Al-Zn-plated steel sheet is not particularly limited and can be appropriately selected depending on the required performance and application. For example, when the fluororesin-coated steel sheet of the present invention is used as a building material, high durability is required, so that a 55% Al-Zn-plated steel sheet or the like can be used.
[0022] The hot-dip Al-Zn plated steel sheet has a plating layer formed on a base steel sheet. The composition of the plating layer is not particularly limited as long as it has good corrosion resistance. For example, the plating layer of the hot-dip Al-Zn plated steel sheet may have a composition containing 20 to 95% by weight of Al, 1 to 3% by weight of Si, and 5% by weight or less of optional added components, with the balance being Zn and unavoidable impurities. When the plating layer has the above-mentioned composition, a dendritic phase and an interdendritic phase surrounding the dendritic phase in a network shape can be formed in the plating layer, and corrosion resistance can be improved.
[0023] From a similar viewpoint, it is preferable that the plating layer has a composition of "plating bath components" defined in JIS G 3321 (2019) 5.1, specifically, a composition containing 50 to 60 mass% Al, 1 to 3 mass% Si, and 5 mass% or less of optional added components, with the remainder being Zn and unavoidable impurities.
[0024] Here, the Al content in the plating layer is 20 to 95 mass%, preferably 50 to 60 mass%, in consideration of the balance between corrosion resistance and operability. If the Al content in the plating layer is at least 20 mass%, dendritic solidification of Al occurs sufficiently. As a result, the main layer mainly contains Zn in a supersaturated state, and is composed of a portion where Al is dendritic solidified (α-Al dendritic phase) and the remaining portion between the dendritic phases (interdendritic phase), and the dendritic phases are laminated in the thickness direction of the plating layer, thereby realizing a structure with excellent corrosion resistance. In addition, the more the α-Al phase dendrites are stacked, the more complex the corrosion progression path becomes, making it more difficult for corrosion to reach the base steel sheet, improving corrosion resistance. On the other hand, if the Al content in the coating layer exceeds 95 mass%, the content of Zn, which has a sacrificial corrosion protection effect against Fe, decreases, deteriorating corrosion resistance. For this reason, the Al content in the coating layer is set to 95 mass% or less.
[0025] In addition, the Si in the coating layer is added to the coating bath for the purpose of suppressing the growth of an interfacial alloy layer formed at the interface with the base steel sheet, and for the purpose of improving corrosion resistance and workability, and is inevitably contained in the main layer. In the case of the hot-dip Al-Zn-coated steel sheet used in the coated steel sheet of the present invention, when the coating bath contains Si and hot-dip coating is performed, the Fe on the steel sheet surface reacts with the Al and Si in the bath to form an alloy consisting of Fe-Al and / or Fe-Al-Si compounds as the base steel sheet is immersed in the coating bath. The growth of the interfacial alloy layer can be suppressed by the formation of this Fe-Al-Si-based interfacial alloy layer. When the Si content in the coating layer is 1% by mass or more, the growth of the interfacial alloy layer can be sufficiently suppressed. On the other hand, when the Si content in the coating layer exceeds 3% by mass, the coating layer is easily precipitated with a Si phase that reduces workability and becomes a cathode site. For this reason, the Si content in the coating layer is set to 3% by mass or less.
[0026] The plating layer contains Zn as a main component of the plating layer. By containing Zn in the plating layer, a sacrificial corrosion protection effect can be obtained, and it is possible to improve the corrosion resistance. On the other hand, when the content of Zn is 80 mass% or less, it is preferable in that the content of Al can be secured and the above-mentioned corrosion resistance due to the dendrite phase and the interdendritic phase can be realized.
[0027] Furthermore, the plating layer may contain 5 mass % or less of optional added components in addition to the above-mentioned Al, Si, and Zn. The optional additive components can be appropriately selected depending on the performance required for the plating layer, and examples thereof include alkaline earth metals such as Ca and Mg, and additive components such as Mn, V, Cr, Mo, Ti, Sr, Ni, Co, Sb, and B. Although these optional components have the effect of further improving corrosion resistance, they may reduce the workability of the plating layer and deteriorate the ultimate elongation of the coated steel sheet, so the content of these optional components is preferably 5 mass% or less.
[0028] The plating layer may contain Mg and / or Ca as the optional additive components from the viewpoint of corrosion resistance. When the plating layer corrodes, Mg and / or Ca are contained in the corrosion product, which improves the stability of the corrosion product and retards the progress of corrosion, resulting in an effect of improving corrosion resistance. The total content of Ca and / or Mg is not particularly limited as long as it is 5 mass% or less, but is preferably 0.01 to 5 mass%. By setting the content to 0.01 mass% or more, a sufficient corrosion retardation effect can be obtained, while by setting the content to 5 mass% or less, the effect does not reach saturation, an increase in production costs can be suppressed, and the composition of the plating bath can be easily controlled. The plating layer preferably contains at least Mg. This is because the plating layer contains Mg, which allows the production of Mg2Si together with Si, and thus provides a corrosion retardation effect. The content of Mg in the plating layer is preferably 0.01 to 5 mass%, and more preferably 2 to 4.9 mass%.
[0029] Furthermore, similar to the alkaline earth metals Ca and Mg as the optional added components, the plating layer may further contain, as the optional added components, one or more selected from Mn, V, Cr, Mo, Ti, Sr, Ni, Co, Sb, and B in a total amount of 5 mass % or less, preferably 0.01 to 5 mass %, since these components have the effect of improving the stability of corrosion products and delaying the progress of corrosion.
[0030] The plating layer contains components of the base steel sheet that are incorporated into the plating due to a reaction between the plating bath and the base steel sheet during plating processing, and unavoidable impurities in the plating bath. The components of the base steel sheet that are incorporated into the plating may contain up to about 2% Fe. Examples of the types of unavoidable impurities in the plating bath include Fe, Cu, Zr, and the like. It is not possible to distinguish and quantify the Fe in the plating layer between that incorporated from the base steel sheet and that in the plating bath. There are no particular limitations on the total content of the unavoidable impurities, but from the viewpoint of maintaining the corrosion resistance and uniform solubility of the plating, it is preferable that the total amount of unavoidable impurities excluding Fe is 1 mass% or less.
[0031] The interfacial alloy layer is a layer of the coating layer that exists at the interface with the base steel sheet, and is an Fe-Al and / or Fe-Al-Si compound that is inevitably produced by an alloying reaction between Fe on the steel sheet surface and Al or Si in the bath, as described above. This interfacial alloy layer is hard and brittle, and if it grows too thick it will become the starting point for cracks during processing, so it is preferable to make it as thin as possible.
[0032] The means for forming the coating layer on the base steel sheet is not particularly limited, and a normal continuous hot-dip galvanizing facility can be used. For example, the base steel sheet is heated to a predetermined temperature in an annealing furnace maintained in a reducing atmosphere, and after annealing, rolling oil and the like adhering to the steel sheet surface are removed and the oxide film is reduced and removed, the steel sheet is immersed in a hot-dip galvanizing bath containing Al and Zn at a predetermined concentration through a snout whose lower end is immersed in the coating bath. The steel sheet immersed in the coating bath is then pulled up above the coating bath via a sink roll, and the coating amount is adjusted by spraying pressurized gas from a gas wiping nozzle arranged above the coating bath toward the surface of the steel sheet, and then cooled by a cooling device to form a coating layer.
[0033] Furthermore, when the coating layer does not contain any optional additives, the critical elongation of the hot-dip Al-Zn coated steel sheet before the formation of the coating film can be improved to about 20% or more by, for example, performing a heat treatment at 200°C for 24 hours. This is believed to be because the coating layer is softened by the Zn that is supersaturated in the aluminum-rich dendritic phase being expelled by the heat treatment. On the other hand, in the case of a coating layer having a composition containing optional added elements, the effect of improving workability by such heat treatment is small, and for example, when 2 to 4.9% of Mg is added as the optional added element, the limit elongation after heat treatment remains less than 5%. Although the reason for this is not yet clear, it is presumed that the high solubility in Al causes it to remain as a solid solution element in the aluminum-rich dendritic phase even after heat treatment, among other things.
[0034] Furthermore, the structure of the plating layer contains a dendritic phase and an interdendritic phase, and the Vickers hardness of the dendritic phase is 10 to 110 Hv. 0.01 It is preferable that the Vickers hardness of the dendritic phase is 10 to 110 Hv. 0.01 By making it smaller, the processing of painted steel sheets The Vickers hardness of the dendrite phase is 110Hv 0.01 If the Vickers hardness of the dendrite phase exceeds 10Hv, there is a risk that sufficient workability cannot be obtained. 0.01 If the hardness is less than 100 Hv, the scratch resistance of the plating layer surface may be reduced. 0.01 It is preferable that the resistance is 30 to 90Hv. 0.01 It is more preferable that:
[0035] The Vickers hardness of the dendrite phase can be measured by embedding a sample of a fluororesin-coated steel sheet in a resin that dries at room temperature, polishing it, selecting the dendrite phase of the plating layer from the exposed cross section, and measuring the Vickers hardness of the selected dendrite phase using a microhardness tester (e.g., Shimadzu Corporation's HMV-G21 microhardness tester). The measurement method complies with JIS Z 2244, and in the case of the plating layer, the Vickers hardness is measured under the condition of an indentation load of 0.98 mN (0.1 gf) (Hv 0.1 ) testing is being carried out.
[0036] (chemical conversion coating) In the fluororesin-coated steel sheet of the present invention, a chemical conversion coating is formed on the plating layer of the hot-dip galvanized steel sheet. By forming a chemical conversion coating on the plating layer, the corrosion resistance of the fluororesin-coated steel sheet can be further improved.
[0037] The type and forming conditions of the chemical conversion coating are not particularly limited, and can be appropriately selected depending on the required performance. For example, it can be formed by a chromate treatment or chromate-free chemical conversion treatment in which a chromate treatment liquid or a chromium-free chemical conversion treatment liquid is applied and then dried without rinsing at a steel sheet temperature of 80 to 300° C. When the working environment and the like are taken into consideration, it is preferable that the chemical conversion coating is formed by a chromate-free treatment (i.e., the chemical conversion coating does not contain chromium).
[0038] (Primer layer) In the fluororesin-coated steel sheet of the present invention, a primer layer is formed between the chemical conversion coating and the topcoat layer. By forming a primer layer between the chemical conversion coating and the topcoat layer, the adhesion of the topcoat layer described below to the hot-dip Al-Zn-plated steel sheet can be further improved, and the corrosion resistance and rust prevention properties can also be further improved.
[0039] The thickness of the primer layer is not particularly limited, and can be appropriately adjusted depending on the required performance. For example, from the viewpoint of achieving both rust prevention and processability, the thickness of the primer layer can be set to 2 to 15 μm. When the thickness is 2 μm or more, sufficient rust prevention is obtained, while when the thickness is 15 μm or less, sufficient processability is ensured.
[0040] Here, the primer layer may contain a rust inhibitor from the viewpoint of improving the rust resistance of the coated steel sheet. The rust inhibitor may be either a chromate type containing chromate or a chromate-free type not using chromate. However, when considering the working environment, etc., a chromate-free type (i.e., the primer layer does not contain chromium) is preferable, and the following describes the chromate-free type primer layer.
[0041] The resin constituting the matrix component of the primer layer is not particularly limited, but from the viewpoints of workability, corrosion resistance, rust prevention, etc., it is preferable to use a polyester-based resin and / or an epoxy-based resin.
[0042] The polyester resin preferably contains a polyester resin having a urethane bond as a main component. Here, as the polyester resin having a urethane bond, a known resin such as a resin obtained by reacting a polyester polyol with a diisocyanate or polyisocyanate having two or more isocyanate groups can be used. Also usable is a resin obtained by reacting a polyester polyol with a diisocyanate or polyisocyanate having two or more isocyanate groups in a state of excess hydroxyl groups (urethane-modified polyester resin) and curing the resin with a blocked polyisocyanate.
[0043] The polyester polyol can be obtained by a known method utilizing a dehydration condensation reaction between a polyhydric alcohol component and a polybasic acid component. The polyhydric alcohol includes glycols and trihydric or higher polyhydric alcohols. Examples of glycols include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, neopentyl glycol, hexylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2-butyl-2-ethyl-1,3-propanediol, methylpropanediol, cyclohexanedimethanol, and 3,3-diethyl-1,5-pentanediol. Examples of trihydric or higher polyhydric alcohols include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, and dipentaerythritol. These polyhydric alcohols can be used alone or in combination of two or more. The polybasic acid is usually a polybasic carboxylic acid, but can be used in combination with a monobasic fatty acid if necessary. Examples of polybasic carboxylic acids include phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, 4-methylhexahydrophthalic acid, bicyclo[2,2,1]heptane-2,3-dicarboxylic acid, trimellitic acid, adipic acid, sebacic acid, succinic acid, azelaic acid, fumaric acid, maleic acid, itaconic acid, pyromellitic acid, dimer acid, and the like, and their acid anhydrides, 1,4-cyclohexanedicarboxylic acid, isophthalic acid, tetrahydroisophthalic acid, hexahydroisophthalic acid, hexahydroterephthalic acid, and the like. These polybasic acids can be used alone or in combination of two or more.
[0044] Examples of the polyisocyanate compound include aliphatic diisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and dimer acid diisocyanate, aromatic diisocyanates such as xylylene diisocyanate (XDI), metaxylylene diisocyanate, tolylene diisocyanate (TDI), and 4,4-diphenylmethane diisocyanate (MDI), and further cyclic aliphatic diisocyanates such as isophorone diisocyanate, hydrogenated XDI, hydrogenated TDI, and hydrogenated MDI, as well as adducts, biurets, and isocyanurates thereof. These polyisocyanate compounds can be used alone or in combination of two or more.
[0045] The polyester resin having a urethane bond has both flexibility and strength, and has the effect of suppressing the occurrence of cracks in the primer layer when processed, etc. In addition, it has a high affinity with chemical conversion coatings containing urethane resins, and contributes to improving the corrosion resistance of processed parts in particular. Here, the hydroxyl value of the polyester resin having a urethane bond is preferably 5 to 120 mgKOH / g, more preferably 7 to 100 mgKOH / g, and further preferably 10 to 80 mgKOH / g, from the viewpoints of solvent resistance, processability, and the like.
[0046] The number average molecular weight of the polyester resin having a urethane bond is preferably 500 to 15,000, more preferably 700 to 12,000, from the viewpoints of solvent resistance, processability, etc. More preferably, it is 800 to 10,000.
[0047] The polyester resin is preferably contained in the primer layer in an amount of 40 to 88% by mass. If it is less than 40% by mass, the binder function of the primer layer is reduced, and if it exceeds 88% by mass, the functions of the inorganic substances described below, such as the inhibitor action, may be reduced. The inorganic substances contained in the primer layer may include vanadium compounds, phosphate compounds, magnesium oxides, etc., which function as inhibitors.
[0048] Examples of the vanadium compound acting as the inhibitor include vanadium pentoxide, metavanadic acid, ammonium metavanadate, vanadium oxytrichloride, vanadium trioxide, vanadium dioxide, magnesium vanadate, vanadyl acetylacetonate, vanadium acetylacetonate, etc. Among these, it is preferable to use a tetravalent vanadium compound or a tetravalent vanadium compound obtained by reduction or oxidation as the vanadium compound. The vanadium compound added to the primer layer may be the same or different from the vanadium compound added to the chemical conversion coating. It is believed that the vanadate compound forms a passive coating with good adhesion by reacting vanadate ions that are gradually dissolved by moisture entering from the outside with ions on the surface of the zinc-based plated steel sheet, thereby protecting the exposed metal parts and exhibiting a rust-preventing effect.
[0049] The vanadium compound content in the primer layer is preferably 4 to 20% by mass, because if it is less than 4% by mass, the inhibitor effect may decrease, leading to a decrease in corrosion resistance, whereas if it exceeds 20% by mass, it may lead to a decrease in moisture resistance of the primer layer.
[0050] The phosphoric acid compound acting as the inhibitor may be, for example, phosphoric acid, ammonium salts of phosphoric acid, alkali metal salts of phosphoric acid, alkaline earth metal salts of phosphoric acid, etc. Among these, it is preferable to use alkali metal salts of phosphoric acid such as calcium phosphate.
[0051] The content of the phosphate compound in the primer layer is preferably 4 to 20% by mass, because if it is less than 4% by mass, the inhibitor effect may decrease, leading to a decrease in corrosion resistance, whereas if it exceeds 20% by mass, it may lead to a decrease in moisture resistance of the primer layer.
[0052] The magnesium oxide acting as an inhibitor has the effect of stabilizing the products generated by early corrosion as poorly soluble magnesium salts. The amount of magnesium oxide added in the primer layer is preferably 4 to 20% by mass. If it is less than 4% by mass, the above effect may decrease, leading to a decrease in corrosion resistance, while if it exceeds 20% by mass, the flexibility of the primer layer may decrease, leading to a decrease in corrosion resistance, particularly in the processed portion.
[0053] The crosslinking agent used in forming the primer layer reacts with the polyester resin having the urethane bond to form a crosslinked coating film, and is preferably a blocked polyisocyanate compound. Examples of the blocked polyisocyanate include polyisocyanate compounds in which the isocyanate group is blocked with alcohols such as butanol, oximes such as methyl ethyl ketoxime, lactams such as ε-caprolactams, diketones such as acetoacetic acid diester, imidazole, imidazoles such as 2-ethylimidazole, or phenols such as m-cresol.
[0054] (Topcoat layer) The coated steel sheet of the present invention further comprises a topcoat layer in addition to the above-mentioned hot-dip Al-Zn plated steel sheet, chemical conversion coating and primer layer. By optimizing the topcoat layer, a coated steel sheet having good corrosion resistance, workability, weather resistance, etc. can be obtained.
[0055] The top coat layer contains a resin component as a matrix, and the resin component contains a polyvinylidene fluoride resin (PVdF resin) and an acrylic resin. The content by mass of the polyvinylidene fluoride resin in the resin component must be 50 to 80%. By including the polyvinylidene fluoride resin in the resin component, it is possible to improve the processability, weather resistance, antifouling properties, etc. of the fluororesin-coated steel sheet.
[0056] When the content by mass of the polyvinylidene fluoride resin in the resin component is 45% or more, the performance (processability, weather resistance, antifouling property, durability, etc.) required for the top coat layer can be sufficiently imparted. From the same viewpoint, the content by mass of the polyvinylidene fluoride resin is preferably 50% or more. In addition, by making the content ratio of the polyvinylidene fluoride resin in the resin component 85% or less by mass, it is possible to suppress a decrease in adhesion of the top coat layer. From the same viewpoint, it is preferable that the content ratio of the polyvinylidene fluoride resin in the resin component is 80% or less by mass.
[0057] The polyvinylidene fluoride resin preferably has a weight average molecular weight of 150,000 to 700,000 and a melting point of 150 to 180° C. An example of such a polyvinylidene fluoride resin is “Kynar 500 (weight average molecular weight: 350,000, melting point: 160 to 165° C.)” manufactured by Arkema.
[0058] The acrylic resin to be mixed with the polyvinylidene fluoride resin preferably has a weight average molecular weight of 50,000 to 200,000. The acrylic resin can be obtained by polymerizing (or copolymerizing) at least one of the following monomers (i) to (iv) (including at least one acrylic monomer) by a conventional method.
[0059] (i) Ethylenic monomers having a hydroxyl group, such as hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate. (ii) Ethylenic monomers having a carboxyl group, such as (meth)acrylic acid, crotonic acid, itaconic acid, fumaric acid, and maleic acid. (iii) Ethylenic monomers copolymerizable with the above-mentioned monomers (1) and (2), such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, and (meth)acrylic acid alkyl esters. (iv) Styrene and styrene derivatives such as α-methylstyrene, o-methylstyrene, m-methylstyrene and p-methylstyrene. Among these monomers, by using a monomer having a functional group such as a hydroxyl group or a carboxyl group, a crosslinking reaction with other reactive components is possible.
[0060] Among the above-mentioned monomers (i) to (iv), it is preferable that 80 mass % or more of the constituent monomer units is at least one selected from acrylic acid alkyl ester monomers or methacrylic acid alkyl ester monomers having an alkyl group of 1 to 8 carbon atoms, such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, and isobutyl methacrylate.
[0061] However, the amount of methyl methacrylate in the acrylic resin is preferably less than 80% by mass. If the amount of methyl methacrylate is 80% by mass or more, the topcoat layer becomes too hard and the processability decreases. The reason why such an alkyl acrylate monomer or alkyl methacrylate monomer is suitable is that it has excellent compatibility with polyvinylidene fluoride resin and also has excellent weather resistance.
[0062] The acrylic resin does not need to be self-crosslinking, but when it is self-crosslinking, it contains a so-called crosslinking monomer having two or more radically polymerizable unsaturated bonds in the molecule. Examples of radically polymerizable monomers include polymerizable unsaturated compounds such as ethylene glycol diacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, 1,3-butylene glycol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, 1,4-butanediol diacrylate, neopentyl glycol diacrylate, 1,6-hexanediol diacrylate, pentaerythritol diacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, glycerol dimethacrylate, glycerol diacrylate, diallyl terephthalate, diallyl phthalate, glycidyl acrylate, and glycidyl methacrylate. The crosslinking monomer can be added up to 20% by mass of the acrylic resin.
[0063] The resin component may be composed only of the polyvinylidene fluoride resin and the acrylic resin, but may also contain other resins such as polyester-based resins, if necessary. The polyester resin includes, for example, polyester resin, silicon-modified polyester resin, and acrylic-modified polyester resin, and as a curing agent for the base resin, a polyisocyanate compound and / or an amino resin can be used.
[0064] The acrylic resin or polyester resin is used in combination with a curing agent, which may be a polyisocyanate compound or an amino resin.
[0065] As the polyisocyanate compound, an isocyanate compound obtained by a general manufacturing method can be used, but it is preferable to use a polyisocyanate compound that can be used as a one-liquid type paint and is blocked with a blocking agent such as phenol, cresol, aromatic secondary amine, tertiary alcohol, lactam, oxime, etc. By using this blocked polyisocyanate compound, it becomes possible to store it in one liquid form, and it becomes easy to use it as a paint.
[0066] Further, more preferred polyisocyanate compounds include HDI and derivatives thereof, TDI and derivatives thereof, MDI and derivatives thereof, XDI and derivatives thereof, IPDI and derivatives thereof, TMDI and derivatives thereof, hydrogenated TDI and derivatives thereof, hydrogenated MDI and derivatives thereof, and hydrogenated XDI and derivatives thereof.
[0067] Furthermore, commercially available isocyanate compounds such as Sumidur (trade name, manufactured by Sumika Covestro Urethane Co., Ltd.), Desmodur (trade name, manufactured by Sumika Covestro Urethane Co., Ltd.), and Coronate (trade name, manufactured by Tosoh Corporation) can also be used.
[0068] When a polyisocyanate compound is used as the curing agent, the compounding ratio [NCO / OH] of the isocyanate group of the polyisocyanate compound to the hydroxyl group in the base resin is preferably 0.8 to 1.2 in terms of molar ratio, and more preferably in the range of 0.90 to 1.10. If the molar ratio of [NCO / OH] is less than 0.8, the curing of the topcoat layer is insufficient, and the desired hardness and strength of the topcoat layer may not be obtained. On the other hand, if the molar ratio of [NCO / OH] is more than 1.2, side reactions between the excess isocyanate groups or between the isocyanate groups and the urethane compound may occur, and the processability of the topcoat layer may decrease.
[0069] As the amino resin as the curing agent, resins obtained by reacting urea, benzoguanamine, melamine or the like with formaldehyde, and those obtained by alkyl etherifying these with alcohols such as methanol and butanol can be used. Specific examples include methylated urea resins, n-butylated benzoguanamine resins, methylated melamine resins, n-butylated melamine resins, and iso-butylated melamine resins.
[0070] Furthermore, commercially available amino resins such as Cymel (trade name, manufactured by Allnex), U-Ban (trade name, manufactured by Mitsui Chemicals, Inc.), and Melan (trade name, manufactured by Hitachi Chemical Co., Ltd.) can also be used.
[0071] When an amino resin is used as the curing agent, the compounding ratio of the amino resin to the base resin (weight ratio of solid contents) is preferably from (95 / 5) to (65 / 35), and more preferably from (90 / 10) to (75 / 25), in terms of base resin / amino resin.
[0072] The amount of the curing agent is preferably 9 to 50% by mass in terms of the ratio of the resin solid content. If it is less than 9% by mass, the hardness of the topcoat layer may be insufficient, and if it exceeds 50% by mass, the processability may be insufficient.
[0073] The top coat layer contains a color pigment in addition to the resin component. The color pigment can be appropriately selected depending on the desired color, additional performance such as heat insulation, etc. Examples of the color pigment include titanium oxide, red iron oxide, carbon black, etc., and these can also be used in combination. Incidentally, the color pigments mentioned above do not include those which fall under the category of inorganic fillers, which will be described later.
[0074] The content of the color pigment in the top coat layer is not particularly limited and can be appropriately adjusted depending on the type of color pigment and the required performance. In view of the fastness of the top coat layer, the total content of the color pigment is preferably 10 to 50 mass %, more preferably 20 to 40 mass %.
[0075] The top coat layer contains, in addition to the resin component and the color pigment, an inorganic filler having an average particle size of 1 to 30 μm and an aspect ratio of 5 or more. Such an inorganic filler can act as a crack propagation inhibitor in the topcoat layer, and can improve the aging workability of the fluororesin-coated steel sheet of the present invention.
[0076] The content of the inorganic filler in the topcoat layer is 0.1 to 20% by mass. From the viewpoint of obtaining an excellent crack propagation suppression effect, the content of the inorganic filler in the topcoat layer must be 0.1% by mass or more, and is preferably 1% by mass or more. Furthermore, from the viewpoint of maintaining the durability and processability of the topcoat layer, the content of the inorganic filler in the topcoat layer must be 20% by mass or less, and is preferably 15% by mass or less.
[0077] The inorganic filler must have an average particle size of 1 to 30 μm, but if the average particle size of the inorganic filler is less than 1, a sufficient crack propagation suppression effect cannot be obtained. From the same viewpoint, the inorganic filler preferably has an average particle size of 2 μm or more. On the other hand, if the average particle size of the inorganic filler exceeds 30 μm, the appearance may deteriorate during roll coating. Therefore, the average particle size of the inorganic filler must be 30 μm or less, and 20 μm or less is preferable. It is preferable that the thickness is less than 10 μm, and more preferable that the thickness is less than 10 μm. The average particle size of the inorganic filler can be obtained, for example, by observing the cross section of the topcoat layer using an electron microscope, and the average particle size can be determined by measuring the longest diameter of each inorganic filler present in multiple observation fields (for example, five fields) and averaging them.
[0078] The aspect ratio of the inorganic filler must be 5 or more, but if the aspect ratio of the inorganic filler is less than 5, a sufficient crack propagation suppression effect cannot be obtained. From the same viewpoint, the aspect ratio of the inorganic filler is preferably 10 or more. On the other hand, if the aspect ratio of the inorganic filler exceeds 75, there is a risk of destruction during preparation and application of the paint. Therefore, the aspect ratio of the inorganic filler is preferably 75 or less. The aspect ratio of the inorganic filler is the ratio of the average particle diameter to the average thickness of the inorganic filler (average particle diameter / average thickness). As described above, the average particle diameter and average thickness of the inorganic filler can be obtained by, for example, observing the cross section of the topcoat layer using an electron microscope, and the aspect ratio can be calculated from the average particle diameter and average thickness of the inorganic filler present in multiple observation fields (for example, five fields).
[0079] The type of the inorganic filler is not particularly limited as long as it satisfies the above-mentioned particle size and aspect ratio. For example, natural mica, synthetic mica, vermiculite, talc, silicon nitride, kaolin, wollastonite, titanate, alumina powder, graphite, glass flake, potassium titanate fiber, sepiolite, gypsum fiber, carbon fiber, aramid fiber, laras fiber, zonolite, etc.; or surface-treated products of these with metal coating, silane coupling, etc. can be used. These inorganic fillers can be used alone or in combination.
[0080] The top coat layer contains, in addition to the resin component, the color pigment, and the inorganic filler, a filler having an average particle size of 1 to 35 μm and a micro Vickers hardness of 50 HV 0.05 Includes organic aggregates that are: Such an organic aggregate can act like a stress relaxant in the topcoat layer, and can improve the aging workability of the fluororesin-coated steel sheet of the present invention.
[0081] The content of the organic aggregate in the topcoat layer is 0.1 to 15% by mass. From the viewpoint of obtaining an excellent stress relaxation effect, the content of the organic aggregate in the topcoat layer must be 0.1% by mass or more, preferably 1% by mass or more, and more preferably 2% by mass or more. Furthermore, from the viewpoint of maintaining the durability and strength of the topcoat layer, the content of the organic aggregate in the topcoat layer must be 15% by mass or less, preferably 12% by mass or less, and more preferably 10% by mass or less.
[0082] The organic aggregate must have an average particle size of 1 to 35 μm, but if the average particle size of the organic aggregate is less than 1, a sufficient crack propagation suppression effect cannot be obtained. From the same viewpoint, the organic aggregate preferably has an average particle size of 2 μm or more, and more preferably has an average particle size of 3 μm or more. On the other hand, if the average particle size of the organic aggregate exceeds 35 μm, the organic aggregate is likely to come off from the top coat layer during bending, so the average particle size of the organic aggregate must be 35 μm or less, preferably 30 μm or less, and more preferably 20 μm or less. The average particle size of the organic aggregate is the average of the shortest diameter and the longest diameter of the organic aggregate. The shortest diameter and the longest diameter of the organic aggregate can be obtained, for example, by observing the cross section of the topcoat layer using an electron microscope, and the average particle size can be calculated by measuring the shortest diameter and the longest diameter of the organic aggregate present in a plurality of observation fields (for example, five fields).
[0083] The micro Vickers hardness of the organic aggregate is 50HV 0.05 The following is required, but The micro Vickers hardness of the aggregate is 50HV 0.05 If the aspect ratio exceeds 45HV, sufficient stress relaxation effect cannot be obtained. 0.05 It is preferable that the value is less than 40HV. 0.05 It is more preferable that: On the other hand, if the micro Vickers hardness of the organic aggregate is less than 10, there is a risk that sufficient durability of the top coat layer cannot be obtained, so the micro Vickers hardness of the organic aggregate is set to 10HV. 0.05 More preferably, it is equal to or greater than this. The micro Vickers hardness of the organic aggregate can be measured by embedding a sample fluororesin-coated steel plate in a room temperature drying resin, polishing it, selecting an organic aggregate from the cross section of the exposed topcoat layer, and using a micro hardness tester (e.g., Shimadzu Corporation's micro hardness tester HMV-G21). The measurement method is in accordance with JIS Z 2244, and is performed under the condition of a load of 0.49 mN (0.05 gf) (HV 0.05 ) testing is being carried out.
[0084] The type of the organic aggregate is not particularly limited as long as it satisfies the above-mentioned particle size and micro Vickers hardness. For example, beads (particles) of acrylic resin, urethane resin, fluororesin, urea resin, acrylic triblock copolymer, butadiene rubber, etc., or surface-treated products of these with functional groups can be used. These organic aggregates can be used alone or in combination.
[0085] The total content of the inorganic filler and the organic aggregate in the topcoat layer is preferably 0.2 to 35% by mass, more preferably 1 to 30% by mass. When the total content of the inorganic filler and the organic aggregate is 0.2% by mass or more, the crack propagation suppression effect and the stress relaxation effect are sufficiently obtained, so that more excellent processability over time can be obtained. On the other hand, when the total content of the inorganic filler and the organic aggregate is 35% by mass or less, the decrease in durability of the topcoat layer can be reliably suppressed.
[0086] The top coat layer may contain other additives in addition to the resin component, the color pigment, the inorganic filler, and the organic aggregate, depending on the purpose and application. Examples of the other additives include metallic pigments such as aluminum powder, pigments such as carbonates and sulfates, various fine particles such as silica fine particles for adjusting gloss, wax, antifoaming agents, and leveling agents. The total content of these other additives in the top coat layer is preferably 10% by mass or less, so as not to impair the effects of the present invention, such as processability over time.
[0087] The coating conditions for forming the topcoat layer are not particularly limited. For example, the coating composition that is the material for the topcoat layer can be applied by a method such as roll coater coating or curtain flow coating. After the coating composition is applied, the topcoat layer can be formed by baking using a heating means such as hot air heating, infrared heating, or induction heating. The temperature of the baking treatment is usually set to a maximum plate temperature of about 240 to 260°C. In addition, in the case of hot air heating, the hot air speed is preferably set to a high speed of 1 to 10 m / sec, preferably 5 to 10 m / sec, on the plate surface.
[0088] Furthermore, the average thickness of the topcoat layer is not particularly limited, but is preferably 10 to 50 μm, and more preferably 12 to 30 μm. If the average thickness of the topcoat layer is less than 10 μm, the durability of the topcoat layer may be reduced, and if the average thickness of the topcoat layer exceeds 50 μm, pinhole defects called popping may easily occur due to bumping of thinner in the paint during baking. EXAMPLES
[0089] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.
[0090] <Examples 1 to 4 of the present invention and Comparative Examples 1 to 3> (Example 1 of the present invention) Plate thickness: 0.35 mm, coating weight: 150 g / m per side 2A hot-dip Al-Zn plated steel sheet was prepared in which a plating layer having a composition of Zn-55%Al-1.6%Si was subjected to skin pass treatment. A vanadium-based chromate-free chemical conversion treatment solution (a chemical conversion treatment solution using urethane resin as the resin component and containing an organic vanadium compound chelated with acetylacetone as the rust-preventive component) was applied to the above hot-dip Al-Zn-plated steel sheet using a bar coater, and the steel sheet was dried at an ultimate temperature of 90°C for a baking time of 10 seconds to obtain a coating weight of 0.2 g / m. 2 The chemical conversion coating was formed so that Thereafter, a primer layer paint having an epoxy-modified urethane resin as a base and vanadium phosphate as an anti-rust pigment was applied onto the above chemical conversion coating layer using a roll coater, and the paint was baked at a steel plate temperature of 210°C for a baking time of 25 seconds to form a primer layer with a film thickness of 5 μm after baking. The steel plate on which the primer layer was formed was water-cooled and dried, and then the resin component was mixed with 30% by mass of PVdF resin and 15% by mass of acrylic resin (total of 45% by mass), 40% by mass of iron-chromium composite oxide ("Black 411" manufactured by Shepherd Color) (average particle size 1.1 μm) as a black pigment, 0.5% by mass of titanium oxide (average particle size 500 nm) as a white pigment, 3% by mass of synthetic mica (average particle size 15 μm, aspect ratio 10) as an inorganic filler, and 3% by mass of acrylic beads (average particle size 20 μm, micro Vickers hardness 20 HV) as an organic aggregate. 0.05 A paint for the topcoat layer containing 1,000g of fluororesin was then prepared. The paint for the topcoat layer was then applied onto the primer layer, and the topcoat layer was formed by baking for 50 seconds at a plate temperature of 250°C in an oven with an atmospheric temperature of 400°C and an average hot air speed of 5m / sec on the plate surface so that the average film thickness after drying would be 20μm, and a coated steel plate (fluororesin coated steel plate) was produced as a sample. The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1. The average particle size and aspect ratio of the inorganic filler, and the average particle size and micro Vickers hardness of the organic aggregate in the topcoat layer were controlled in advance to be within the above-mentioned ranges.
[0091] (Example 2 of the present invention) The organic aggregate in the topcoat layer is not acrylic beads, but PTFE aggregate (average particle size 18 μm, micro Vickers hardness 10HV 0.05 A coated steel sheet sample was produced under the same conditions as in Example 1 of the present invention, except that 1 mass % of the fluorine-containing compound was used. The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1.
[0092] (Example 2 of the present invention) As the organic aggregate in the topcoat layer, polytetrafluoroethylene (PTFE) aggregate (average particle size 18 μm, micro Vickers hardness 10 HV) was used instead of acrylic beads. 0.05 A coated steel sheet sample was prepared under the same conditions as in Example 1 of the present invention, except that 1 mass % of the sintered body was used. The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1.
[0093] (Example 3 of the present invention) A sample coated steel sheet was prepared under the same conditions as in Example 1 of the present invention, except that 3 mass% of talc (average particle size 20 μm, aspect ratio 10) was used as the inorganic filler in the top coat layer instead of synthetic mica. The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1.
[0094] (Example 4 of the present invention) Prior to the formation of the chemical conversion coating layer, the hot-dip Al-Zn-plated steel sheet is annealed at an atmospheric temperature of 200°C for 12 hours, and the Vickers hardness of the dendritic phase in the coating layer is adjusted to 10 to 110 HV. 0.1 Range A coated steel sheet sample was produced under the same conditions as in Example 1 of the present invention, except that the above-mentioned conditions were changed. The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1.
[0095] Comparative Example 1 A coated steel sheet sample was prepared under the same conditions as in Invention Example 1, except that the topcoat layer did not contain acrylic beads as an organic aggregate and synthetic mica as an inorganic filler. The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1.
[0096] Comparative Example 2 A sample coated steel plate was prepared under the same conditions as in Example 1 of the present invention, except that the topcoat layer did not contain acrylic beads as an organic aggregate or synthetic mica as an inorganic filler, but contained 3 mass% synthetic silica (average particle size 4 μm). The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1.
[0097] Comparative Example 3 The organic aggregate in the topcoat layer is not acrylic beads, but polyimide aggregate (average particle size 20 μm, micro Vickers hardness 60 Hv 0.05 A coated steel sheet sample was produced under the same conditions as in Example 1 of the present invention, except that 1 mass % of the fluorine-containing compound was used. The conditions of the topcoat layer of the sample coated steel sheets are also shown in Table 1.
[0098] <Evaluation> Each of the samples of coated steel sheets obtained as described above was evaluated as follows.
[0099] (1) Workability and aging processability A bending test was carried out on each sample of coated steel plate according to JIS G 3322. When a test piece with a width of 75 mm was bent 180 degrees, the inner distance was expressed by the number of plates, and the limit number of plates (T) at which no cracks occurred in the bent surface coating was taken as No-Crack T. The smaller this No-Crack T, the better the workability. This bending test was carried out immediately after the sample was made and after it was kept at 50°C for 72 hours (accelerated aging), which is equivalent to storing the sample for 3 months in summer. The results of no crack T immediately after the sample was made and after accelerated aging are shown in Table 1. In addition, for the bending test after accelerated aging, the aged workability was evaluated according to the following criteria. The evaluation results are shown in Table 1. 〇: 6T or less, which is practical for siding applications, etc. ×: Over 6T
[0100] [Table 1]
[0101] The results in Table 1 show that the samples of the present invention are superior in processability over time compared to the samples of the comparative examples. [Industrial Applicability]
[0102] According to the present invention, it is possible to provide a coated steel sheet which is excellent in workability over time while maintaining other physical properties such as workability and weather resistance at a good level.
Claims
1. A coated steel sheet having a chemical conversion coating, a primer layer and a top coat layer formed on a hot-dip Al-Zn-plated steel sheet, The top coat layer comprises a resin component containing a polyvinylidene fluoride resin and an acrylic resin, the polyvinylidene fluoride resin being present in an amount of 50 to 80% by mass; A color pigment; 0.1 to 20 mass% of an inorganic filler having an average particle size of 1 to 30 μm and an aspect ratio of 5 or more; Average grain size is 1 to 35 μm and micro Vickers hardness is 50 HV 0.05 0.1 to 15% by mass of organic aggregate, A fluororesin-coated steel sheet comprising:
2. 2. The fluororesin-coated steel sheet according to claim 1, wherein a total content of the inorganic filler and the organic aggregate in the top coat layer is 0.2 to 35 mass%.
3. 3. The fluororesin-coated steel sheet according to claim 1, wherein the coating layer of the hot-dip Al-Zn-coated steel sheet has a composition containing 20 to 95 mass% Al, 1 to 3 mass% Si, 5 mass% or less of optional added components, and the balance consisting of Zn and unavoidable impurities.
4. 4. The fluororesin-coated steel sheet according to claim 3, characterized in that the plating layer has a composition containing 50 to 60 mass% Al, 1 to 3 mass% Si, 5 mass% or less of optional added components, and the balance consisting of Zn and unavoidable impurities.
5. The plating layer has a dendritic phase and an interdendritic phase, and the Vickers hardness of the dendritic phase is 10 to 110 HV. 0.1 The fluororesin-coated steel sheet according to claim 3 or 4, characterized in that
Citation Information
Patent Citations
Coating composition excellent in processability and abrasion resistance and coated metal plate
JP1997221621A
Coating composition excellent in scratch resistance, abrasion resistance and durability and metallic plate coated therewith
JP1998219182A
Stainless steel plate coated with transparent fluororesin having high film hardness and excellent wear resistance
JP2001137775A
Coated hot dip al-zr alloy plated steel sheet having excellent workability and corrosion resistance
JP2002363722A
Coated steel sheet for exterior
JP2003071980A